2015
DOI: 10.1063/1.4937154
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the nonlinear dynamics of driven particles in supercooled liquids in terms of an effective temperature

Abstract: In active microrheology the mechanical properties of a material are tested by adding probe particles which are pulled by an external force. In case of supercooled liquids, strong forcing leads to a thinning of the host material which becomes more pronounced as the system approaches the glass transition. In this work we provide a quantitative theoretical description of this thinning behavior based on the properties of the Potential Energy Landscape (PEL) of a model glass-former. A key role plays the trap-like n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 49 publications
(111 reference statements)
1
23
0
Order By: Relevance
“…More recently, in Ref. [5] the potential energy landscape approach was used in order to calculate the population distribution of different metabasin energies in the presence of the external force. It was shown that the energy distribution of the system maintains a Gaussian form but becomes shifted towards higher energies, fact that yield the authors to characterize the effect in terms of an effective temperature whose dependence on the force coincides with Eq.…”
Section: Origin Of the Force Dependent Effective Temperaturementioning
confidence: 99%
See 4 more Smart Citations
“…More recently, in Ref. [5] the potential energy landscape approach was used in order to calculate the population distribution of different metabasin energies in the presence of the external force. It was shown that the energy distribution of the system maintains a Gaussian form but becomes shifted towards higher energies, fact that yield the authors to characterize the effect in terms of an effective temperature whose dependence on the force coincides with Eq.…”
Section: Origin Of the Force Dependent Effective Temperaturementioning
confidence: 99%
“…Comparison between simulation data (symbols) taken from Ref. [5] and the results for the effective mobility given by Eq. (24) (lines) assuming the periodic potential U (x) given in Eq.…”
Section: Origin Of the Force Dependent Effective Mobility: The Mean F...mentioning
confidence: 99%
See 3 more Smart Citations